How much do money, inconvenience and pollution matter? : analysing households' demand for large-scale recycling and incineration - Huhtala, Anni (Academic Press, 1999)
Dwindling landfill space and environmental problems with old landfills have forced municipalities to search for new methods to handle solid wastes. The contingent valuation method is used to study householdsŽchoice between two alternative waste disposal services, large-scale recycling and incineration, which differ in convenience and air pollution effects. The present study seeks to evaluate how intense peopleŽs preferences are in monetary terms. To capture the benefits of waste management, the willingness-to-pay (WTP) estimates are then included in the comparison of disposal options. The motivation is that if only costs are compared and environmental impacts are neglected in evaluating public provision of waste disposal services, choices which are unfavourable from a social point of view may be made.
Keywords: Ma; kierrätys; jätehuolto; waste disposal; recycling; waste management; contingent valuation; incineration